Monetary Policy and Domestic Investment in Nigeria: The Role of the Inflation Rate - Ezeibekwe Obinna Franklin (Economics and Business)
Economic theory suggests that monetary policy can be used to stabilize an economy. However, the ability of monetary policy targets—interest rates and money supply—to stabilize an economy depends on their ability to achieve price stability. Using data from 1981 to 2018 and applying the vector error correction model, this paper seeks to determine how the changes in the inflation rate affect the ability of monetary policy tools to stabilize the Nigerian economy and stimulate investment. Empirical results suggest that the impact of the interest rates on investment depends on the level of the inflation rate. The size of the effect of interest rates on investment gets weaker as the inflation rate increases suggesting that monetary policy tools, such as the monetary policy rate (MPR), that directly change the interest rates are robust stabilization tools during periods of declining inflation rates but not relevant during periods of rising inflation rates. This is attributable to low bank lending rates. Additionally, the impact of the money supply target on investment does not depend on the level of the inflation rate. This suggests that monetary policy tools, such as open market operations, that directly change the money supply can be relevant stabilization tools during economic booms and recessions. As a result, the Central Bank of Nigeria should work to deepen the scale, capacity, and efficiency of its open market operations by ensuring that most of the people can participate with minimal transaction cost and by making different financial instruments available.